Daily intake of baru (Dipteryx alata Vog.), a Cerrado native almond, promotes changes in the intestinal microbiota of individuals with obesity: A pilot study - Campos, Stéphani Borges; Oliveira Filho, Josemar Gonçalves de [UNESP]; Santos, Daiane Costa dos; Egea, Mariana Buranelo (Elsevier, 2024)
The Brazilian Cerrado biome is rich in plant biodiversity, with fruits that have unique sensory characteristics and high nutritional quality. Among the various fruits, baru (Dipteryx alata Vog.) has attracted the attention of researchers because of its high lipid, protein, carbohydrate, fiber, and micronutrient (minerals and vitamins) contents. The present study evaluated the effects of regular consumption of baru almonds for over 60 days on the biochemical and anthropometric profiles and fecal microbiota of obese individuals. A pilot study was conducted on 15 individuals with obesity who were instructed to consume a 20-gram portion of baru almonds throughout the day. The body composition was assessed using anthropometric measurements. Blood pressure, glucose levels, lipid profile, serum insulin and iron contents, and fecal microbiota composition were determined at baseline (day 0) and after 60 days. Baru almond consumption contributed to changes in biochemical parameters, improved HDL cholesterol levels, and reduced total and LDL cholesterol levels. Some positive changes in the microbiota composition after consuming baru almonds include a decrease in the Faecalibacterium family and an increase in the Provotella genus. Therefore, ingesting baru almonds can modulate gut microbiota of individuals with obesity.
Keywords: Baru almond; Faecalibacterium; Gut microbiota; Lipids; Obesity